Stop being 'clever', just be smart - Abd Razak, Dzulkifli (2009)
THE Malaysia Productivity Corporation held a timely conference on "Competitiveness: Enhancing Competitiveness through Creativity and Innovation" last week. The aim was to provide more engagements in realising the aspirations to develop a highincome economy where growth is driven by productivity in the context of creativity and innovation. The corporation, which was set up 43 years ago, is the national body responsible for the enhancement of productivity, quality and competitiveness, and is committed to work for a better standard of living of Malaysians.